Effects of Water, Sanitation, Handwashing, and Nutritional Interventions on Environmental Enteric Dysfunction in Young Children: A Cluster-randomized, Controlled Trial in Rural Bangladesh. (8th April 2019) - Lin, Audrie; Ali, Shahjahan; Arnold, Benjamin F; Rahman, Md Ziaur; Alauddin, Mohammad; Grembi, Jessica; Mertens, Andrew N; Famida, Syeda L; Akther, Salma; Hossen, Md Saheen; Mutsuddi, Palash; Shoab, Abul K; et al.
Abstract: Background: We hypothesized that drinking water, sanitation, handwashing (WSH), and nutritional interventions would improve environmental enteric dysfunction (EED), a potential contributor to stunting. Methods: Within a subsample of a cluster-randomized, controlled trial in rural Bangladesh, we enrolled pregnant women in 4 arms: control, WSH, child nutrition counseling plus lipid-based nutrient supplements (N), and nutrition plus WSH (N+WSH). Among the birth cohort, we measured biomarkers of gut inflammation (myeloperoxidase, neopterin), permeability (alpha-1-antitrypsin, lactulose, mannitol), and repair (regenerating gene 1β) at median ages 3, 14, and 28 months. Analysis was intention-to-treat. Results: We assessed 1512 children. At age 3 months, compared to controls, neopterin was reduced by nutrition (–0.21 log nmol/L; 95% confidence interval [CI], –.37, –.05) and N+WSH (–0.20 log nmol/L; 95% CI, –.34, –.06) interventions; similar reductions were observed at 14 months. At 3 months, all interventions reduced lactulose and mannitol (–0.60 to –0.69 log mmol/L). At 28 months, myeloperoxidase was elevated in the WSH and nutrition arms (0.23–0.27 log ng/mL) and lactulose was higher in the WSH arm (0.30 log mmol/L; 95% CI, .07, .53). Conclusions: Reductions in permeability and inflammation at ages 3 and 14 months suggest that the interventions promoted healthy intestinal maturation; however, by 28 months, the WSH and nutrition arms showed elevated EED biomarkers. These results underscore the importance of developing a better understanding of EED pathophysiology and targeting interventions early in childhood, when they are likely to have the largest benefit to intestinal health. Clinical Trials Registration: NCT01590095. Abstract : Intensive water, sanitation, hygiene, and nutritional interventions reduced environmental enteric dysfunction at ages 3 and 14 months. We recommend targeting interventions early in childhood during the critical period when they are likely to have the largest benefit to intestinal health.